Diversity of Book-Tax Conformity in Asean 4: Philippines, Indonesia, Malaysia, and Singapore - Febrina, Fiska; Rachmawati, Nurul Aisyah (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2023)
This research aimed to determine the diversity of Book-Tax Conformity (BTC) between countries and industries in ASEAN 4. This research is descriptive-qualitative research. This research uses a sample of manufacturing and non-manufacturing companies listed on the Philippine Stock Exchange, Indonesia Stock Exchange, Bursa Malaysia, and Singapore Exchange. Limited from 2012-2018. The results of this research indicate that during the period 2012–2018 the movement of the BTC level in ASEAN 4 varies every year. Based on the results of different tests that have been carried out between industries in each country in ASEAN 4, it can be seen that there is a diversity of BTC between industries in the Philippines, Indonesia, and Malaysia. Meanwhile, in Singapore, there is no diversity of BTC between industries because there are no differences in tax regulations regarding the provisions of the inventory valuation method and the depreciation method regulated by the Singapore taxation authority for the manufacturing industry and non-manufacturing industries in Singapore in presenting the taxable profit report. Tujuan penelitian ini adalah untuk mengetahui keragaman Book-Tax Conformity (BTC) antar negara dan antar industri di ASEAN 4. Penelitian ini merupakan penelitian kualitatif deskriptif. Penelitian ini menggunakan sampel perusahaan manufaktur dan non manufaktur yang terdaftar di Bursa Efek Filipina, Bursa Efek Indonesia, Bursa Malaysia, dan Bursa Singapura. Dibatasi dari tahun 2012 hingga 2018. Hasil penelitian ini menunjukkan bahwa selama periode 2012 hingga 2018 pergerakan level BTC di ASEAN 4 bervariasi setiap tahunnya. Berdasarkan hasil uji beda yang telah dilakukan antar industri di masing-masing negara di ASEAN 4, terlihat adanya keragaman BTC antar industri di Filipina, Indonesia, dan Malaysia. Sedangkan di Singapura, tidak terdapat diversitas BTC antar industri karena tidak ada perbedaan peraturan perpajakan mengenai ketentuan metode penilaian persediaan dan metode penyusutan yang diatur oleh otoritas perpajakan Singapura untuk industri manufaktur dan industri non-manufaktur di Singapura dalam menyajikan laporan laba kena pajak.